Upaya Mengoptimalkan Kemampuan Lari Cepat dengan Menggunakan Alat Bantu Pembelajaran Pendidikan Jasmani - Donald, Hendri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
The aim of this class action research was to reach the best ability in sprint technique using the tool in learning sport and health for the students at sixth grade at MIN Sungai Beringin. There were 27 students with 13 male students and 14 female students. The class action research using cycle procedure consists of planning, acting, observation and reflexion. The research is a qualitative research which based on the data have gotten that have been taken from observation and described based on the note in the field while learning. Based on the research which was have been done. The result of the research there were developing ability of sprint skill. In the first cycle The earlier students ability in sprint was 9.97, In the first cycle 0,41 and the next cycle is 8,88 so the students ability increase 0.91 . For the students criteria achievement minimum /KKM (Kreteria Ketuntasan Minimal) . In earlier condition, They had 29.63% and first cycle70.73% and the second cycle 88.89%. The increasing condition of KKM is 59.26%